Improved natural melanin production by Aspergillus nidulans after optimization of factors involved in the pigment biosynthesis pathway - Medeiros, William Bartolomeu [UNESP]; Medina, Kelly Johana Dussán [UNESP]; Sponchiado, Sandra Regina Pombeiro [UNESP] (Springer Nature, 2022)
Background: Melanin is a natural pigment that can be applied in different fields such as medicine, environment, pharmaceutical, and nanotechnology. Studies carried out previously showed that the melanin produced by the mel1 mutant from Aspergillus nidulans exhibits antioxidant, anti-inflammatory, and antimicrobial activities, without any cytotoxic or mutagenic effect. These results taken together suggest the potential application of melanin from A. nidulans in the pharmaceutical industry. In this context, this study aimed to evaluate the effect of factors L-tyrosine, glucose, glutamic acid, l-DOPA, and copper on melanin production by the mel1 mutant and to establish the optimal concentration of these factors to maximize melanin production. Results: The results showed that l-DOPA, glucose, and copper sulfate significantly affected melanin production, where l-DOPA was the only factor that exerted a positive effect on melanin yield. Besides, the tyrosinase activity was higher in the presence of l-DOPA, considered a substrate required for enzyme activation, this would explain the increased production of melanin in this condition. After establishing the optimal concentrations of the analyzed factors, the melanin synthesis was increased by 640% compared to the previous studies. Conclusions: This study contributed to elucidating the mechanisms involved in melanin synthesis in A. nidulans as well as to determining the optimal composition of the culture medium for greater melanin production that will make it possible to scale the process for a future biotechnological application.
Keywords: Aspergillus nidulans; Fungal pigment; l-DOPA; Melanin; Response surface methodology